Patients' and providers' perceptions of the preventability of hospital readmission: a prospective, observational study in four European countries. Issue 12 (22nd June 2017) - van Galen, Louise S; Brabrand, Mikkel; Cooksley, Tim; van de Ven, Peter M; Merten, Hanneke; So, Ralph KL; van Hooff, Loes; Haak, Harm R; Kidney, Rachel M; Nickel, Christian H; Soong, John TY; Weichert, Immo; et al.
Abstract : Objectives: Because of fundamental differences in healthcare systems, US readmission data cannot be extrapolated to the European setting: To investigate the opinions of readmitted patients, their carers, nurses and physicians on predictability and preventability of readmissions and using majority consensus to determine contributing factors that could potentially foresee (preventable) readmissions. Design: Prospective observational study. Readmitted patients, their carers, and treating professionals were surveyed during readmission to assess the discharge process and the predictability and preventability of the readmission. Cohen's Kappa measured pairwise agreement of considering readmission as predictable/preventable by patients, carers and professionals. Subsequently, multivariable logistic regressionidentified factors associated with predictability/preventability. Setting: 15 hospitals in four European countries Participants: 1398 medical patients readmitted unscheduled within 30 days Main Outcome(s) and Measure(s): (1) Agreement between the interviewed groups on considering readmissions likely predictable or preventable;(2) Factors distinguishing predictable from non-predictable and preventable from non-preventable readmissions. Results: The majority deemed 27.8% readmissions potentially predictable and 14.4% potentially preventable. The consensus on predictability and preventability was poor, especially between patients and professionals (kappas ranged from 0.105 to 0.173). The interviewed selected different factors as potentially associated with predictability and preventability. When a patient reported that he was ready for discharge during index admission, the readmission was deemed less likely by the majority (predictability: OR 0.55; 95% CI 0.40 to 0.75; preventability: OR 0.35; 95% CI 0.24 to 0.49). Conclusions: There is no consensus between readmitted patients, their carers and treating professionals about predictability and preventability of readmissions, nor associated risk factors. A readmitted patient reporting not feeling ready for discharge at index admission was strongly associated with preventability/predictability. Therefore, healthcare workers should question patients' readiness to go home timely before discharge.